Effects of Nitrogen and Light Intensity on the Astaxanthin Accumulation in Motile Cells of Haematococcus pluvialis - Li, Feng; Cai, Minggang; Wu, Yanqi; Lian, Qingsheng; Qian, Zuyuan; Luo, Jiansen; Zhang, Yulei; Zhang, Ning; Li, Changling; Huang, Xianghu (Frontiers in Marine Science, 2022)
The dietary supplementation of Haematococcus pluvialis is a natural, safe, and sustainable method for fish pigmentation. However, astaxanthin-rich H. pluvialis cysts have a poor effect in pigmenting salmonid flesh due to their rigid and thick cell wall. H. pluvialis thin-walled motile cells have recently attracted attention due to their potential advantages in maintaining compound stability, easy digestion, enhancing the bioavailability of carotenoids, and reducing production costs. This study aimed to investigate the effect of various nitrogen concentrations and light intensities on astaxanthin production in motile cells. We first investigated the effect of four different concentrations of nitrogen on astaxanthin accumulation in motile cells. According to the results, the motile cells had the highest astaxanthin concentration and content under the 0 N condition. Then, we compared the differences in astaxanthin production in motile cells under three different light intensities under 0 N conditions. The results showed that after four days of treatment, the protoplasts of the motile cells in the medium light (ML) group and the high light (HL) group had distinct granularity. The cell mortality rate in the HL group reached more than 15%, which was significantly higher than that in the low light (LL) and ML groups, indicating that high light intensity was not suitable for inducing motile cells to accumulate astaxanthin. There were no significant differences between the LL and ML groups in astaxanthin content, motile cells percentage, and cell mortality rate. Considering these indicators, we recommended inducing motile cells to produce astaxanthin under low light conditions because it is more economical in terms of electricity consumption. This study added to the knowledge that nitrogen and light affects the accumulation of astaxanthin in H. pluvialis motile cells. The results would help determine the optimal nitrogen and light conditions in astaxanthin production from motile cells.